Konseling Gestalt Berbasis Islam dalam Upaya Meningkatkan Kemampuan Regulasi Diri Santri di Pondok Pesantren Al-Falaah Pandak Bantul Yogyakarta - Nurviyanti Cholid (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
This research was motivated by there is an opportunity for the use of Islamic scholarship concepts that serve as material in Islamic guidance and counseling services to improve self-regulation of santri. the final result proposed in this study is guidance and counseling Gestalt-based Islam can improve self-regulation of santri. The purpose of this study is to determine the role of guidance and counseling Gestalt-based Islam to improve the regulation of boarding school boarding school Al-Falaah Pandak Bantul Yogyakarta. This type of research is qualitative descriptive research. The population of this study is all students aged 13-14 years. The sample in this research is determined by random assignment technique from a population. The sample in this research is determined by random assignment technique from the population. The total number of samples in this study were 24 santri given intervention in the form of guidance and counseling Gestalt Islam based Data collected by questionnaire, observation, and interview. Gestalt counseling on the basis of Islam is quite effective in improving the self-regulating ability of the students at the boarding school Al-Falaah Pandak Bantul Yogyakarta. Therefore, the findings of the research results can be used as a reference in developing Islamic counseling and counseling to develop the potential of an individual.